Studies of the imaginary: origins and paths - Pérez Morales, Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The proposed reflections are the result of the doctoral research (2008) supported by the theoretical and methodological principles of the Theory of the Imaginary, which unveiled through its methodology (symbolic hermeneutics) the need to establish contextual readings about the imaginary and the symbolic, as well as the understanding of these phenomena (the imaginary and the symbolic), concerning different models from the traditional, deriving an epistemological position that claims the place of methodologies, epistemologies and emerging theories, such as those discussed in the text. In this sense, the paper begins with the paradigmatic transformations studied by Boaventura de Sousa Santos (2008) and then deals with the relevance, validity and importance of studies of the imaginary from the theoretical perspective of Gilbert Durand.